Pindborg tumor associated with a supernumerary tooth: a case report - Morais, Hannah Gil de Farias; Silva, Weslay Rodrigues da; Andrade, Ana Cláudia de Macêdo; Silva, Nelmara Sousa e; Xerez, Mariana Carvalho; Santos, José Wittor de Macêdo; Germano, Adriano Rocha; Costa, Antônio de Lisboa Lopes (Autopsy and Case Reports, 2022)
The calcifying epithelial odontogenic tumor is a rare benign neoplasm that accounts for approximately 1% of all odontogenic tumors. Most of the cases occur in the posterior mandible, and a few involve the maxilla. Despite their relatively indolent biological behavior, tumors in the maxilla tend to grow fast. We report the case of a 33-year-old female patient exhibiting swelling in the right maxilla. An isodense area associated with an impacted supernumerary tooth was found on imaging examination. The histopathologic diagnosis was a calcifying epithelial odontogenic tumor. The treatment of choice was surgical removal of the lesion and associated dental elements. The patient has been followed up for 11 months and shows no signs of recurrence. Besides describing this case, we reviewed the literature on the association of calcifying epithelial odontogenic tumors with supernumerary teeth and found two case reports addressing this subject.